Determinants of customer acceptance and usage of mobile hotel reservation apps (MHRA): An exploratory factor analysis / Mohd Noor Ismawi Ismail ... [et al.] - Ismail, Mohd Noor Ismawi; Hanafiah, Mohd Hafiz; Hemdi, Mohamad Abdullah; Sumarjan, Norzuwana; Azdel, Abdul Aziz (Universiti Teknologi MARA Cawangan Selangor and UiTM Press, 2020)
The purpose of this study is to apply exploratory factor analysis (EFA) to assess the determinants of customer acceptance and usage of mobile hotel reservation apps (MHRA). The Unified Theory of Acceptance and Use of Technology (UTAUT2) model is adopted in this study. Through an online survey, the UTAUT2 determinants were administered to 422 Malaysian hotel customers who booked hotel rooms through MHRA. EFA, using Principal Component Analysis with Varimax Rotation, indicated a 34-item, with 7 factors final solution with the following subscales: Effort Expectancy (6 items); Habit (4 items); Hedonic Motivation (5 items); Performance Expectancy (5 items); Price Value (4 items); Social Influence (5 items); and Facilitating Condition (5 items). The finding confirms that the items to each of these domains are consistent with the UTAUT2 proposed determinants. This paper enables future researchers to expand the concept of MHRA by providing validated constructs for assessing technology adoption and usage among hotel customers. The significance of the study as well as its implications for research and practice are discussed. Suggestions are also made for future research.